Some Policy Considerations in the Drafting of New Towns Legislation - Daniel R. Mandelker (Washington University Law Quarterly, 1965)
As American policy-makers set the stage for a program of new town development, public attention has largely been directed toward two important elements of that program: the nature of the new town communities we plan to build and the conditions under which federal aid will be extended for their assistance. To the extent that new town development will be carried on by public agencies, the content of the state enabling legislation under which these public agencies will operate must also receive serious consideration. This Article will draw on the English experience with their new towns in order to examine two basic issues of legislative policy-the problems arising in the selection of new town sites, and the methods to be utilized in the planning and construction of new town communities.
Keywords: New Towns